2005
DOI: 10.1097/01.qai.0000143603.94728.b2
|View full text |Cite
|
Sign up to set email alerts
|

Nonfinancial Factors Associated With Decreased Plasma Viral Load Testing in Ontario, Canada

Abstract: Injection drug users, younger individuals, and residents of Toronto used fewer viral load tests than other individuals, even when financial barriers to testing were removed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…There are only a few studies from developed countries examining the frequency of VL testing [3], [8], [9], [10], [11], [12]. Haubrich et al [8] conducted a randomized trial in the early CART era in 1996/97 to compare the outcome of frequent VL measurement with infrequent VL measurement.…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few studies from developed countries examining the frequency of VL testing [3], [8], [9], [10], [11], [12]. Haubrich et al [8] conducted a randomized trial in the early CART era in 1996/97 to compare the outcome of frequent VL measurement with infrequent VL measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Carrico et al 21 observed five-fold higher HIV viral load among those endorsing regular stimulant use compared to those who did not report stimulant use. A history of substance use also has implications for care, with HIV infected individuals with substance use histories less likely to receive highly active antiretroviral therapies (HAART) 22 , and other clinical assessments such as viral load testing 23 . Hepatitis C (HCV) is observed in 60-90% of HIV infected drug users.…”
Section: Substance Use and Health Outcomesmentioning
confidence: 99%
“…HIV-infected persons with a history of drug use are less likely to receive antiretroviral treatment Fairfield, Libman, Davis, & Eisenberg, 1999;Junghans et al, 1999;Lucas, Chaisson, & Moore, 1999;Mocroft et al, 1999;Murri et al, 1999;Palella et al, 1998;Strathdee et al, 1998;Turner et al, 2001), viral load testing (Laine et al, 2001;Raboud et al, 2005), or lipid screening (Korthuis et al, 2004); experience greater HIV-related symptoms (Mathews et al, 2000); and have higher hospitalization rates Gebo, Diener-West, & Moore, 2001;Schoenbaum, Lo, & Floris-Moore, 2002;Shapiro et al, 1999) compared with men who acquired HIV through sex with other men.…”
Section: Introductionmentioning
confidence: 99%